Outbreak of TEM-24-producing Enterobacter aerogenes in an intensive care unit and dissemination of the extended-spectrum beta-lactamase to other members of the family enterobacteriaceae. - Neuwirth, C (1996)
We report an outbreak of Enterobacter aerogenes in an intensive care unit (ICU) and two medicine departments that produced the extended-spectrum beta-lactamase TEM-24, which was difficult to detect by disk agar diffusion. The strains were compared by DNA restriction fragment length polymorphism after pulsed-field gel electrophoresis following cleavage with XbaI. This typing method indicated that a single strain, first isolated in the ICU, spread throughout the other medical departments as a result of patient transfer. We also observed the transfer in vivo of the plasmid encoding TEM-24 from the strain of Enterobacter aerogenes to different strains of Escherichia coli and Citrobacter freundii in the ICU. It therefore appears that the epidemic involved results from two events: dissemination of one strain of Enterobacter aerogenes and dissemination of the plasmid encoding TEM-24 among various members of the family Enterobacteriaceae.